Hydrogen propulsion for civil aviation: an introduction scenario - Pantelis, Isidoros; Huete, Jon; Nalianda, Devaiah; Jarzębowska, Elżbieta; Pilidis, Pericles (ISABE, 2022)
Civil aircraft that fly medium and long ranges consume a large fraction of civil aviation fuel, injecting an important amount of aviation carbon into the atmosphere. Decarbonising solutions must consider this sector in a holistic manner. Hydrogen is increasingly seen as a key solution. There is a number of major issues to resolve. One of them is the provision of appropriate airport infrastructure. A philosophical-analytical scenario feasibility is proposed here based on an airliner family, previously proposed by the authors to assist in the elimination of carbon dioxide emissions from civil aviation. The family comprises six airliner models derived (not retrofits) from existing state of the art airliners. The objective of the philosophical investigation presented here is to explore the gradual implementation of airport infrastructure considering geographical and traffic characteristics. The outcome is a plausible and effective scenario where a gradual introduction of Hydrogen fuel is proposed where for a few decades Hydrogen will coexist with conventional fuels and drop-in Sustainable Aviation Fuels. This scenario proposes a first generation of six very large hydrogen hubs to cover very large traffic centres to make in the first instance deep inroads into civil aviation carbon emissions. A second generation of 16 hydrogen hubs is also proposed that would enable a global span. These two generations of hydrogen hubs could enable a very wide introduction of hydrogen in the long term by catalysing cost reductions with volume and experience, in the long-term delivering 3rd, 4th and nth generations of hydrogen hubs where reliance on carbon fuels is gradually reduced until they have been fully displaced in the long term.
Keywords: Hydrogen; Aviation; Introduction into Market; Sustainability